Analisa Dampak Bahasa Iklan Di Media Sosial Terhadap Penjualan Di Dian Optikal Padang - Saunir, Ihsan (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
Advertising is one of the factors that support the increase in sales volume. Advertising is very influential on sales volume, each company assumes that the greater the advertising costs incurred will affect the increase in sales. This study aims to examine the effect of advertising costs on sales volume at Dian optical. This study uses a quantitative method, which is of the correlation type and data taken for 2 years starting in 2021-2022 and the calculation uses monthly data consisting of Advertising Costs and Sales Volume. Data collection was carried out using documentation and interview methods. The data analysis used is simple linear regression analysis and significant testing using the t test. The test results using the t test produce a positive and significant effect of Advertising Costs on Sales Volume with t count = 3,791 greater than t table = 2.074 with an error rate of 5%.